Algoritmos para alocação de rota e comprimento de onda com restrições de energia e da camada física em redes ópticas - Nogueira, Pedro Henrique Tolentino de Melo (2014)
This dissertation proposes two new algorithms for routing and wavelength allocation EA-RWA (Energy Aware Routing and Wavelength Assigment) and IEA-RWA (Impairment and Energy Aware Routing and Wavelength Assigment). The algorithms have the characteristic, improve energy efficiency in dynamic transparent optical networks, the first being simpler, because it does not care about the imperfections of the physical layer. The EA-RWA is compared with a traditional RWA / classic that does not take into account at the time of admission of the physical layer connections restrictions nor energy consumption algorithm. Have the IEA-RWA is compared with a RWA algorithm that takes into account the constraints (IA-RWA) physical layer. Numerical simulations show that the IEA-RWA performs better in many aspects